Advances in allergic skin disease, anaphylaxis, and hypersensitivity reactions to foods, drugs, and insects in 2009 - Sicherer, Scott H.; Leung, Donald Y.M. (Journal of allergy and clinical immunology, 2010)
This review highlights some of the research advances in anaphylaxis and hypersensitivity reactions to foods, drugs, and insects, as well as advances in allergic skin disease that were reported in the Journal in 2009. Among key epidemiologic observations, several westernized countries report that more than 1% of children have peanut allergy, and there is some evidence that environmental exposure to peanut is a risk factor. The role of regulatory T cells, complement, platelet-activating factor, and effector cells in the development and expression of food allergy were explored in several murine models and human studies. Delayed anaphylaxis to mammalian meats appears to be related to IgE binding to the carbohydrate moiety galactose-α-1,3-galactose, which also has implications for hypersensitivity to murine mAb therapeutics containing this oligosaccharide. Oral immunotherapy studies continue to show promise for the treatment of food allergy, but determining whether the treatment causes tolerance (cure) or temporary desensitization remains to be explored. Increased baseline serum tryptase levels might inform the risk of venom anaphylaxis and might indicate a risk for mast cell disorders in persons who have experienced such episodes. Reduced structural and immune barrier function contribute to local and systemic allergen sensitization in patients with atopic dermatitis, as well as increased propensity of skin infections in these patients. The use of increased doses of nonsedating antihistamines and potential usefulness of omalizumab for chronic urticaria was highlighted. These exciting advances reported in the Journal can improve patient care today and provide insights on how we can improve the diagnosis and treatment of these allergic diseases in the future.